Online Learning Using Audio-visual for Elementary School Students during the Covid-19 Pandemic - Ayupratiwi, Trisya; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Bumi Publikasi Nusantara, 2022)
The COVID-19 pandemic has greatly affected the world of education, where all schools for all levels were closed. This causes learning to take place online or full study at home. Various efforts were made to attract students' interest in learning, one of the efforts made by the teacher was to make learning videos with the aim of students being able to understand the lessons. The purpose of this study is to find out how online learning using audio-visual media can influence students to increase interest in learning. The subject taken in this study were elementary schools’ students from Bandung, Indonesia. The data collection technique uses a questionnaire that will be distributed by us to students, this questionnaire must be filled out before the research begins and after the research is carried out or pre-test and post-test. The result of the research show that the average of post-test score of students is 88% greater than the average pre-test score of 67% so the difference is 21%. The conclusion of this study is there is a good influence in video learning and also shows positive results on student learning outcomes.